Study of kinetic model for fungal spore germination under dynamic conditions: Case study on germination of Penicillium expansum spores - Panuluk Boonruang; Nuttapol Lerkkasemsan (My University, 2023)
The germination of fungal spores under non-isothermal conditions has been studied for several years, however, no mathematical model has been able to describe them suitably. Therefore, in this paper, we developed a new model to clarify the understanding of fungal spore germination under non-isothermal conditions by considering the effects of magnitude of condition change and difference in phase of spore during condition change on kinetic parameters, i.e., the mean rate of germination (μ) and the time that half of spores had germinated (th). To combine both effects into our new model, it was necessary to develop other two new models. The first model was used for estimating the swelling time of spores. The second model was the relationship between th vs μ. After we had completed both models and successfully combined both effects into the new model for fungal spore germination under non-isothermal conditions, the new model was validated against experimental data on germination of Penicillium expansum spores in the literature. The prediction results showed that the new model well described the germination of this fungus under non-isothermal conditions.
Keywords: Spore germination; Isothermal process; Microbial Inactivation Methods